Medial prefrontal glutamate response to acute stress is associated with social subordination in female rhesus macaques - Michael T. Treadway; Samantha A. Betters; Jessica A. Cooper; Chun-Xia Li; Xiaodong Zhang; Vasiliki Michopoulos (Translational Psychiatry)
Abstract Chronic psychosocial stress is associated with increased risk of psychiatric disorders. Magnetic resonance spectroscopy (MRS) in humans has been used to show that glutamate levels in medial prefrontal cortex (mPFC) following acute stress exposure adapt to recent chronic stress levels. Here, we sought to determine the presence of this glutamate stress response adaptation in rhesus macaques, whose societies are maintained by dominance relationships that are enforced by agonistic interactions and result in chronic stress phenotypes seen in humans. We tested the hypothesis that change in mPFC glutamate after an acute stressor would be moderated by behavioral factors related to social subordination in a manner similar to that previously observed in humans. Seventeen adult female rhesus monkeys (Macaca mulatta, 13–23 yrs.) were observed over ten weeks to collect behavioral data and then received two MRS scans. The first scan occurred after acute stress manipulation involving relocation and isolation. The second control scan occurred after acclimation to the new location. As expected, we found that a behavioral measure of social subordination predicted an adaptive glutamate response such that animals experiencing more submissive behavior asymmetry (a behavioral measure related to social subordination) exhibited an attenuated glutamate response to the acute stressor. These data establish the use of MRS to measure the adaptive glutamate stress in non-human primates and will help further our understanding of the neurobiology of stress adaptation.